2020
DOI: 10.1055/s-0040-1713445
|View full text |Cite
|
Sign up to set email alerts
|

Chylous Ascites and Lymphoceles: Evaluation and Interventions

Abstract: Kinmonth introduced lymphangiography in 1955 and it became an important tool in the diagnosis and treatment of malignant disease. The technique, based on bipedal approach, was difficult and time-consuming which limited its use in clinical practice. Cope is the father of percutaneous lymphatic interventions and he was the first person to access and intervene on the lymphatic system. After his initial work published on 1999, there has been an expansion of the lymphatic embolization techniques, particularly since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 86 publications
(150 reference statements)
1
21
0
Order By: Relevance
“…The incidence of postoperative lymphatic leakage during our study period was 14.4% after renal transplant, which is well within the .6–33.9% range of several transplant centers 1–4 . On the other hand, the incidence of lymphatic leakage after a liver transplant was 11.7%, which is higher than the reported range of .6–4.7% 5–7 .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The incidence of postoperative lymphatic leakage during our study period was 14.4% after renal transplant, which is well within the .6–33.9% range of several transplant centers 1–4 . On the other hand, the incidence of lymphatic leakage after a liver transplant was 11.7%, which is higher than the reported range of .6–4.7% 5–7 .…”
Section: Discussionsupporting
confidence: 77%
“…Other studies showed that embolization also offers the advantage of reducing the need for repeat treatments. 3 A systemic review comprising 52 retrospective case series which used traditional methods for treating lymphoceles after renal transplant reported a recurrence rate of 31% after sclerotherapy and 50% with catheter drainage. 26 We did not experience any leak recurrence in our study patients that achieved initial clinical success.…”
Section: Embolizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mainstay of the treatment of postoperative chylous ascites is conservative therapy [24]. Surgical intervention is only indicated for refractory cases.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a predictive nomogram for the individualized probability of chylous ascites following right hemicolectomy with The mainstay of the treatment of postoperative chylous ascites is conservative therapy [24]. Surgical intervention is only indicated for refractory cases.…”
Section: Discussionmentioning
confidence: 99%